The antimicrobial peptide gramicidin S alters proliferation and inhibits adhesion of L929 cell line fibroblasts - Alabedalkarim, N. M.; Berest, V. P.; Moiseieva, N. M.; Bozhok, G. A.; Bondarenko, T. P. (Biophysical Bulletin, 2023)
Background: Natural antimicrobial peptides are used in the fight against pathogens resistant to existing synthetic antibiotics. The non-specific mechanism of cytostatic action of antimicrobial peptides, in particular gramicidin S, against bacteria is also effective for damaging the cells of neoplasms. The existence of such a property in a registered antibiotic will indicate its antineoplastic potential and can be used to expand the spectrum of its therapeutic application.Aim of work is to clarify the possible antitumor effect of the antimicrobial peptide gramicidin S.Materials and Methods: Using the methods of confocal laser microscopy and light microscopy, the morphological and functional features of connective tissue cells under the influence of gramicidin S in the concentration range 0.5–50 μg/ml were studied using L929 fibroblasts cell culture. The cell area, nucleus area, and nucleus-to-cytoplasm ratio were determined. To study the migratory and proliferative activity of cells in vitro, the “scratch assay” was used, the confluency of the monolayer of cells was evaluated, morphometric studies were performed, and the relative area of the scratch was measured after 24, 48, and 72 hours.Results: The lytic effect of gramicidin S in a concentration of 50 μg/ml on L929 cells was established, in concentrations of 0.5 μg/ml and 5.0 μg/ml, the antibiotic increases the synthetic activity of cells and stimulates the proliferation of fibroblasts in a monolayer. Cell anisomorphism is more pronounced in the presence of 5.0 μg/ml gramicidin S added to the culturing medium during monolayer formation, while a one-third of the cells in the sample form a population that is morphologically different from other cells in the culture. The addition of gramicidin S at non-lytic concentrations of 0.5 and 5.0 μg/ml to unattached fibroblasts reliably inhibits monolayer formation. Under the influence of 5.0 μg/ml gramicidin S, the rate of monolayer formation is low, even despite the significant content of cells with a high nuclear-cytoplasmic ratio. The kinetics of filling the cell monolayer defect using the “scratch assay” shows that GS in concentrations of 0.5 and 5.0 μg/ml can control the migratory and proliferative properties of L929 cells.Conclusions: The effect of gramicidin S on the morphometric parameters of cells depends on the concentration of the peptide and the cell status in the culture. GS corrupts the adhesive properties of L929 fibroblasts in monolayer cell culture and the rate of cell monolayer formation. Cells at the stage of attachment and monolayer formation were most sensitive to non-lytic concentrations of GS. Inhibition of the adhesive properties of connective tissue cells by gramicidin S is a new non-canonical effect of a known antimicrobial drug, which may indicate the possibility of using gramicidin S as an anti-neoplasm agent.